(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This study investigates the discursive features of cultural identity representation in English-language and Uzbek media. The relevance of the research is обусловлена the growing influence of media discourse on the construction of cultural meanings in the context of globalization and digital communication. The aim of the study is to identify linguocultural and discursive strategies through which cultural identity is constructed in media texts. The research employs discourse analysis, content analysis, and linguocultural interpretation. The empirical data consist of approximately 80 media texts drawn from news and online platforms. The findings suggest that English-language media tend to emphasize individualization, inclusivity, and global identity, whereas Uzbek media foreground collective values, national traditions, and cultural continuity. It is argued that media discourse functions as a powerful mechanism for shaping cultural identity.